Do different adhesives influence the color stability and fluorescence of composite restorations after aging? - de Souza, Claudia Simoes [UNESP]; da Costa Silva, Thamirys [UNESP]; Tsutsumi, Mariana Sati Cantalejo [UNESP]; Lima, Glivia Queiroz [UNESP]; Queiroz, Mariana Elias [UNESP]; Strazzi-Sahyon, Henrico Badaoui; Maluly-Proni, Ana Teresa [UNESP]; Briso, André Luiz Fraga [UNESP]; Santos, Paulo Henrique dos [UNESP] (FapUNIFESP (SciELO), 2023)
This study aimed to evaluate the influence of dental adhesive color on the chromatic stability and fluorescence intensity of composite resin restorations of different thicknesses. Ninety bovine enamel samples were obtained and restored with resin composite varying thicknesses of restorative material and enamel (1.0 mm enamel and 1.0 mm composite; 1.5 mm enamel and 0.5 mm composite; 0.5 mm enamel and 1.5 mm composite). The restorations were made of composite resin (Opallis E-bleach H) using different types of dental adhesives: Ambar, Ambar APS, and Single Bond Universal (n=10). The samples were subjected to color measurement tests in a spectrophotometer using CIEDE2000 and fluorescence intensity measurements before and after aging in a red wine coloring solution. Data were subjected to analysis of variance (ANOVA) and Tukey's test (α = 0.05). There were no statistically significant changes in color stability or fluorescence intensity for restorations made of different materials or thicknesses (p>0.05). Single Bond Universal showed greater color stability at 0.5 mm thickness (ΔE00 = 4.4 ± 1.6) compared to other thicknesses of the same material (p=0.003), as well as a greater difference in fluorescence intensity after aging at 1.5 mm thickness (-414.9 ± 103.8) compared to other materials (p=0.0002). Overall, it was concluded that the different adhesive systems did not influence the color stability and fluorescence of restorations of different thicknesses.
Keywords: color; composite resins; dentin-bonding agents; fluorescence